Examination of IL-6 and CRP Levels in Missed Abortus Cases - Sapmaz, Ekrem; Celik, Aygen; Bulut, Vedat; Ilhan, Fulya; Hanay, Fethi (Galenos Yayincilik, 2006)
Objective: To examine serum IL-6, CRP, leukocyte, neutrophil and platelet levels of pregnant women diagnosed as missed abortus and healthy pregnant women in a similar pregnancy week. Setting: Firat University, School of Medicine, Obstetrics and Gynaecology Department, Elazig. Material and method: Twenty five pregnant women diagnosed as missed abortus (G1) and 25 healthy pregnant women in similar weeks of pregnancy (G2) were included in a prospective, case-controlled, non-randomized study. IL-6, CRP, leukocyte, neutrophil and platelet levels were analyzed in the patients'serums. Spearman correlation analysis (rs, n, p) was conducted between IL-6 and CRP, and between leukocyte and neutrophil values. Mann Whitney U test was used for ordinal and continuous data. P<0,05 was considered significant. Results: IL-6 level (pg/ml), (mean +/- SD), (16,6 +/- 2,4 vs. 2 +/- 0,2), CRP level (mg/L), (15,4 +/- 2,4 vs. 0,7 +/- 0,1), leukocyte level (103/mu L), (12 +/- 0,2 vs. 8 +/- 0,2) and neutrophil level (103/mu L), (9 +/- 0,2 vs. 5,7 +/- 0,2) were found significantly higher in missed abortus cases, when compared to healthy pregnant women (p< 0,05, Mann Whitney U test). Platelet values were found similar, but slightly lower in the missed abortus group (13/mu L) (267 +/- 7 vs. 281 +/- 9) (p>0,05, Mann Whitney U test). A highly positive correlation was found between IL-6 and CRP and between leukocyte and neutrophil values (CRP rs=0,85/leukocyte rs=0,75/Neutrophil rs=0,8, p=0,000, n=50). Conclusion: IL-6, CRP, leukocyte and neutrophil levels in pregnant women diagnosed as missed abortus are significantly higher than those in healthy pregnant women. This is inconsistent with the classical view of T helper 1/T helper 2 activity change.
Keywords: Missed abortus; IL-6; CRP; T helper 1/T helper 2 activity